Final answer:
To find the value of (g*f)(-1), first calculate f(-1), which is 6, and then use this value to calculate g(6), resulting in 28.
Step-by-step explanation:
The question asks us to find the value of the composition of two functions, (g*f)(x), evaluated at x = -1. Given f(x) = 3x^2 - 2x + 1 and g(x) = 4x + 4, the composite function (g*f)(x) means g(f(x)).
To find this, we first evaluate f(-1):
f(-1) = 3(-1)^2 - 2(-1) + 1 = 3 + 2 + 1 = 6.
Now we use this result to evaluate g(f(-1)) which is g(6):
g(6) = 4(6) + 4 = 24 + 4 = 28.
Therefore, the value of (g*f)(-1) is 28.